State-Crime Nexus on the Myanmar Border: The Symbiosis of the Political Economy of the Military Junta and Border Guard Forces in the Yatai New City Ecosystem - Dita Amanda Prastya; Honest Dody Molasy; Agung Purwanto (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2025)
The 2021 military coup in Myanmar precipitated a collapse in state governance, creating a vacuum often assumed to be the primary driver of organized crime. However, the rapid expansion of Yatai New City in Myawaddy suggests a more complex dynamic. This study investigates the political economy of the Yatai New City, specifically the interaction between foreign investors, the Karen Border Guard Forces (BGF), and the Military Junta. Employing the State–Crime Nexus framework and a qualitative approach based on source triangulation, this research challenges the "ungoverned space" narrative. The findings reveal that the persistence of the cyber-fraud industry in Yatai is not a symptom of state absence but the result of a symbiotic ecosystem. In this arrangement, the BGF provides security and logistical infrastructure, foreign investors supply capital and technology, and the Junta grants structural impunity in exchange for political loyalty and economic survival amidst international sanctions. This study concludes that the "scam state" formation in Myanmar represents a strategic adaptation of authoritarian power, implying that international interventions must target the political-economic alliances sustaining these operations rather than treating them solely as law enforcement issues.